(3GdfGehS GdCYXe hGdbGehS GdCbOe aj eYQaI bOQ GdfHj Udi Gddg Ydjg hSdes - (3YHO GdcQje Hf EHQGgje GdcjdGfjs
(3ChdgG (B:s
(3CeG HYO agPg QSGdI efj Edi YTGb MVQI GdceGd hoeMHj HgLI GdLeGd hoeQjOj fSNI GdLdGd s
(3BNQgG (B:s
(3dCfge Chd ef QChg aj Cced Ndbg hdJcf gPg GdebGdI BNQ gPg GdQSGdI hGddg Gdehab ddUhGH s
(3GdfSNI HgG MhGTs
(3cJGH bGH bhSjf hoedJbi GdfGehSjfs
(3GdJhKjbGJ GdeQLYjI (B:s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1922s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQGdcJH GdeUQjI s
Keywords: (3GdJUha hGdBOGH GdTQYjIs